Seeing shapes in clouds: On the performance-cost trade-off for heterogeneous infrastructure-as-a-service - Inggs,G; Thomas,DB; Constantinides,G; Luk,W (2015)
In the near future FPGAs will be available by the hour, however this newInfrastructure as a Service (IaaS) usage mode presents both an opportunity anda challenge: The opportunity is that programmers can potentially traderesources for performance on a much larger scale, for much shorter periods oftime than before. The challenge is in finding and traversing the trade-off forheterogeneous IaaS that guarantees increased resources result in the greatestpossible increased performance. Such a trade-off is Pareto optimal. The Paretooptimal trade-off for clusters of heterogeneous resources can be found bysolving multiple, multi-objective optimisation problems, resulting in anoptimal allocation of tasks to the available platforms. Solving theseoptimisation programs can be done using simple heuristic approaches or formalMixed Integer Linear Programming (MILP) techniques. When pricing 128 financialoptions using a Monte Carlo algorithm upon a heterogeneous cluster of MulticoreCPU, GPU and FPGA platforms, the MILP approach produces a trade-off that is upto 110% faster than a heuristic approach, and over 50% cheaper. These resultssuggest that high quality performance-resource trade-offs of heterogeneous IaaSare best realised through a formal optimisation approach.